Peningkatan Pengetahuan dan Keterampilan Kader Posyandu dalam Deteksi Dini Stunting di Wilayah Kerja Puskesmas Sukabangun Kecamatan Delta Pawan Kabupaten Ketapang - Tri Eko Sumarto; Elly Trisnawati (Public Health Department, Faculty of Health Science University Muhammadiyah Bengkulu, 2022)
Background: Lack of understanding of Posyandu cadres and lack of measuring instruments (anthropometry) can affect the precision of measurement and interpretation in children with nutritional problems, particularly stunting. This study intends to examine if Posyandu cadres' knowledge of early stunting detection in the Sukabangun Public Health Center working region. Method: This study employs a quasi-experimental approach with a pre-test and post-test for a single group. This study's population consisted of 81 Posyandu cadres, and the sample size was 37. Results: The data were analyzed using a frequency test, specifically the paired sample t-test if the data were normal and the Wilcoxon test if they were not. The knowledge level of Posyandu cadres increased from 48.6% to 81.1% as a result. The proficiency level of Posyandu cadres in reading MCH books increased from 40.5% to 78.4%. In the meantime, the proficiency of Posyandu cadres in anthropometric measurements increased to 73% from 21% for infants and to 91% from 54% for children. Based on the bivariate analysis, there were disparities in the level of knowledge among Posyandu cadres ranging from 2.59 to 7.84. In addition, the degree of proficiency in reading MCH books increased from 5.27 to 11.46, stunting detection skills in toddlers increased from 2.03 to 6.73, and early detection skills of child stunting increased from 5.81 to 13.46. Therefore, the training was deemed effective overall. Conclusion: The training method for early detection of stunting at the research site is effective.